Application of sulfate ion fixation in internal sulfate attack: The gel containing barium salt - Kaiwei Liu; Yawen Sun; Shansan Shen; Daosheng Sun; Aiguo Wang; Yueming Wang (Case Studies in Construction Materials, 2024)
Sulfate attack is one of the most important factors affecting the durability of concrete, and the corrosion sources of internal sulfate attack (ISA) mostly come from the raw materials of concrete. Adding corrosion resistance admixtures to concrete is one of the most effective ways to prevent internal sulfate attack. By wrapping barium salt with SA gel, the modified barium chloride admixture (MB) is obtained which can exist stably in concrete and release barium ions to form barium sulfate in a sulfate environment. The modified barium salt has little effect on the cement workability and hydration process and even can improve the mechanical properties slightly. When the MB content reaches 6% (MB-6), the strength improvement effect is most obvious. Compared with the P-0, the 7d compressive strength of MB-6 is increased by 9.14%, and the 28d compressive strength is increased by 5.77%. It can be seen by SEM that the amount and crystal size of ettringite in the cement mixed with admixtures are reduced. The corrosion resistance of the matrix can be further improved by using a modified barium chloride-silica fume composite admixture (MB-F). After 90 days of internal sulfate attack, the strength of the MB-F even improves slightly. When the modified barium chloride to silica fume ratio is 4:6, the cement-based material achieved the best resistance to internal sulfate attack. In addition to MB, which can make sulfate ions fixation and inhibit the formation of ettringite, silica fume can also consume calcium hydroxide and generate more C-S-H gel, which compacts the weak part of the matrix and greatly improves the resistance to internal sulfate attack of cement-based materials. It provides the possibility for the application of modified barium salt in external sulfate attack.